X-4(x+1)=x/4-3

Simple and best practice solution for X-4(x+1)=x/4-3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for X-4(x+1)=x/4-3 equation:



X-4(X+1)=X/4-3
We move all terms to the left:
X-4(X+1)-(X/4-3)=0
We multiply parentheses
X-4X-(X/4-3)-4=0
We get rid of parentheses
X-4X-X/4+3-4=0
We multiply all the terms by the denominator
X*4-4X*4-X+3*4-4*4=0
We add all the numbers together, and all the variables
-1X+X*4-4X*4-4=0
Wy multiply elements
-1X+4X-16X-4=0
We add all the numbers together, and all the variables
-13X-4=0
We move all terms containing X to the left, all other terms to the right
-13X=4
X=4/-13
X=-4/13

See similar equations:

| 4-3(x-2)=7 | | 5x(-5+5)-5+5x=-25 | | 13+3x+17=23+3x | | ‐4x+3x=2 | | 3+19c=-35 | | 8/9m-1/9=5/72 | | 4x+9+9x-6=81 | | x/3+12=22 | | 4x=1.5x+12 | | 3x=2.5x+10 | | 2(2)x-3=-2 | | -16-4x=-8x-8= | | -26-4x=-8x-8= | | 180-(3x-10)=3x-1 | | 8(7-5n)+6n=294 | | Y=11x^2-396 | | 19+2x-18=x+13 | | O.25+15=0.06x+20 | | 13-w=42 | | 3(x-2)^2+81=0 | | 4x-4=-4+2x+18 | | b+(b+45)+90+(2b-90)+1.5=540 | | 9,500+30=500x | | -2(16n-3)-8=82= | | 21+4y=27 | | −51=−3+8c | | 10+8a=100 | | 1x+-46x=-45x | | x-9+5x-33=24 | | Y=1000*1.01^x | | 3x+4=5x+6x= | | |x-5|-1=0 |

Equations solver categories